A Review on Effect of Building Integrated Photovoltaic Placement and its Potency in Generating Electrical Energy - Rudianto, B.; Ekasiwi, S.N.N.; Antaryama, I.G.N. (IPTEK Journal of Proceedings Series, 2018)
BIPV is an integral part of the building envelope such as the roof or the facade. There is a difference of Building Integrated Photovoltaic placement between the location in the equator region and other regions. The study aims to know the effect of BIPV placement and its potency in generating electrical energy. The study reviews previous research related topics of BIPV in all regions. The study shows that BIPV placement is determined by the sun’s position that producers incidence angle. Incidence angle should fall perpendicularly on a surface to obtain the high of an intensity of solar irradiation. Therefore, most of BIPV placement in the equator region are on rooftops while in the regions far from equator not only on rooftops but also on facades. Roofs are so far considered to be the ideal location for BIPV placement since roofs provide the best solar energy generation. The potency of BIPV can be explored in building design with the variation of orientation and shape to increase the building surfaces for getting solar potential.